Computational Methods in Multiphase Flow V 2009
DOI: 10.2495/mpf090241
|View full text |Cite
|
Sign up to set email alerts
|

Velocity and turbulence measurements of oil-water flow in horizontal and slightly inclined pipes using PIV

Abstract: Oil-water flows in horizontal and slightly inclined pipes are investigated using Particle Image Velocimetry (PIV). PIV offers a powerful non-invasive tool to study such flow fields. The experiments are conducted in a 15 m long, 56 mm diameter, inclinable steel pipe using Exxsol D60 oil (viscosity 1.64 mPa s, density 790 kg/m 3 ) and water (viscosity 1.0 mPa s, density 996 kg/m 3 ) as test fluids. The test pipe inclination is changed in the range from 5° upward to 5° downward. The experiments are performed at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…5). These are also regions of high shear rates in single and multiphase flows (Kumara et al, 2009;Schmitt, 2008).…”
Section: Axial Stressesmentioning
confidence: 98%
See 1 more Smart Citation
“…5). These are also regions of high shear rates in single and multiphase flows (Kumara et al, 2009;Schmitt, 2008).…”
Section: Axial Stressesmentioning
confidence: 98%
“…The applications of PIV to oil-water flows are limited (Chinaud et al, 2017;Kumara et al, 2010aKumara et al, , 2010bKumara et al, , 2009Morgan et al, 2017Morgan et al, , 2013Morgan et al, , 2012Voulgaropoulos and Angeli (2017) and none has been reported when drag reducing polymers are present. Kumara et al (2010a) carried out measurements in a 15 m long, 56 mm ID stainless steel pipe, at 0 o and 5 o pipe inclinations, using water and Exxsol D60 oil (density 790 kg/m 3 and viscosity 1.64 mPa s) and found good agreement between LDA and PIV measurements.…”
Section: Introductionmentioning
confidence: 99%